Child hunger and the protective effects of supplemental nutrition assistance program (SNAP) and alternative food sources among Mexican-origin families in Texas border colonias - Sharkey, Joseph R (BioMed Central, 2013)
BACKGROUND: Nutritional health is essential for children’s growth and development. Many Mexican-origin children who reside in limited-resource colonias along the Texas-Mexico border are at increased risk for poor nutrition as a result of household food insecurity. However, little is known about the prevalence of child hunger or its associated factors among children of Mexican immigrants. This study determines the prevalence of child hunger and identifies protective and risk factors associated with it in two Texas border areas. METHODS: This study uses 2009 Colonia Household and Community Food Resource Assessment (C-HCFRA) data from 470 mothers who were randomly recruited by promotora-researchers. Participants from colonias near two small towns in two South Texas counties participated in an in-home community and household assessment. Interviewer-administered surveys collected data in Spanish on sociodemographics, federal food assistance program participation, and food security status. Frequencies and bivariate correlations were examined while a random-effects logistic regression model with backward elimination was used to determine correlates of childhood hunger. RESULTS: Hunger among children was reported in 51% (n = 239) of households in this C-HCFRA sample. Bivariate analyses revealed that hunger status was associated with select maternal characteristics, such as lower educational attainment and Mexican nativity, and household characteristics, including household composition, reliance on friend or neighbor for transportation, food purchase at dollar stores and from neighbors, and participation in school-based nutrition programs. A smaller percentage of households with child hunger participated in school-based nutrition programs (51%) or used alternative food sources, while 131 households were unable to give their child or children a balanced meal during the school year and 145 households during summer months. In the random effects model (RE = small town), increased household composition, full-time unemployment, and participation in the National School Lunch Program were significantly associated with increased odds for child hunger, while participation in Supplemental Nutrition Assistance Program (SNAP) and purchasing food from a neighbor were significantly associated with decreased odds for child hunger. CONCLUSIONS: This study not only emphasizes the alarming rates of child hunger among this sample of Mexican-origin families, but also identifies economic and family factors that increased the odds for child hunger as well as community strategies that reduced the odds. It is unsettling that so many children did not participate in school-based nutrition programs, and that many who participated in federal nutrition assistance programs remained hungry. This study underscores the importance of identifying the presence of child hunger among low-income Mexican-origin children in Texas border colonias and increasing access to nutrition-related resources. Hunger-associated health inequities at younger ages among colonia residents are likely to persist across the life span and into old age.